2016
DOI: 10.1007/s11270-016-2999-4
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Polycyclic Aromatic Hydrocarbons in Mangrove Sediments Under Different Strategies: Natural Attenuation, Biostimulation, and Bioaugmentation with Rhodococcus erythropolis T902.1

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are pollutants that occur in mangrove sediments. Their removal by bacteria often depends on specific characteristics as the number of benzene rings they possess and their solubility. Their removal also depends on environmental factors, such as pH, temperature, oxygen, and the ability of the endogenous or exogenous microflora to metabolize hydrocarbons. With the aim of treating mangrove sediments polluted by hydrocarbons in a biological way, a biodegradation experiment wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…was identified, previously enriched with a mixture of PAHs including naphthalene, anthracene, fluoranthene and pyrene, each in the concentration order of 10-30 mg•L −1 , revealed potential for PAHs degradation. Several other studies have highlighted the potential of species form the genera Pseudomonas, Rhodococcus erythropolis and Acinetobacter johnsonii to degrade PAHs compounds [55][56][57]. Nevertheless, in the present study, the mixture of PAHs was the carbon source that allowed a lower biomass growth and a lower abundance of hydrocarbons-degraders, when compared with acetate and petroleum.…”
Section: Discussionmentioning
confidence: 58%
“…was identified, previously enriched with a mixture of PAHs including naphthalene, anthracene, fluoranthene and pyrene, each in the concentration order of 10-30 mg•L −1 , revealed potential for PAHs degradation. Several other studies have highlighted the potential of species form the genera Pseudomonas, Rhodococcus erythropolis and Acinetobacter johnsonii to degrade PAHs compounds [55][56][57]. Nevertheless, in the present study, the mixture of PAHs was the carbon source that allowed a lower biomass growth and a lower abundance of hydrocarbons-degraders, when compared with acetate and petroleum.…”
Section: Discussionmentioning
confidence: 58%
“…The proper selection of bacterial strains is always a crucial step, and well-known hydrocarbon degraders may succeed or fail depending on the environment they are introduced to [11,32]. In favorable conditions, bioaugmentation with even a single strain resulted in the effective removal of hydrocarbons [61] and even within one species, one could find a difference among individual strains in this regard [62].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we observed biodegradation of pharmaceutical pollutants by bacteria of the genus Rhodococcus (class Actinomycetia)-a group of extremely tolerant mycolic acid-containing nocardioform actinomycetes, which are structurally, physiologically, and biochemically fit for decomposition of lipophilic organic compounds. Rhodococci are among the dominant microorganisms in anthropogenically disturbed biotopes and also participate in their restoration [14][15][16][17][18]. The ubiquity and localization of Rhodococcus spp.…”
Section: Introductionmentioning
confidence: 99%